2004
DOI: 10.1097/01.ju.0000136315.80057.99
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Small Renal Cell Carcinoma: Evaluation of Growth Rate, Histological Grade, Cell Proliferation and Apoptosis

Abstract: The growth rate of RCCs correlates with apoptosis and grade. Most incidentally found RCCs are slow growing. However, those with certain histopathological features can grow rapidly and have a poor prognosis. More attention should be given to the observation of small renal masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
1
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(88 citation statements)
references
References 20 publications
4
75
1
8
Order By: Relevance
“…The reason for this difference is not clear. The gender distribution however is concordant with other studies both locally and internationally i.e., M: F=1.9-2:1 (Kato, 2004;Lafit, 2011).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The reason for this difference is not clear. The gender distribution however is concordant with other studies both locally and internationally i.e., M: F=1.9-2:1 (Kato, 2004;Lafit, 2011).…”
Section: Discussionsupporting
confidence: 79%
“…In a local study conducted at SIUT, furhman's grade II was the most common (Latif and Mubarak, 2011). In a Japanese study, furhman's grade was I in 38%, II in 44.4% and III in 16% cases (Kato, 2004). In one Spanish study, nuclear grade 2 according to Fuhrman's Classification System accounts for 42.9% of the cases (Bocardo et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the increased detection of tumours by imaging techniques, such as ultrasound (US) and computerised tomography (CT), the number of incidentally diagnosed RCCs has increased. These tumours are more often smaller and of lower stage (17,18). In this study there were 2 incidentally found renal tumours (pT1a and pT1b).…”
Section: Discussionmentioning
confidence: 90%
“…With respect to this treatment paradigm, an important underlying assumption, one not supported by several case series, [17][18][19][20][21][22] is that all small renal masses have the universal capacity to grow and metastasize. This assumption, however, has several possible flaws.…”
Section: Discussionmentioning
confidence: 99%